SYMBOLIC SIGNS OF THE HAPPINESS CONCEPT: LINGUOCULTURAL ANALYSIS - Ivan I. Kaftan (Sovremennye Issledovaniâ Socialʹnyh Problem, 2022)
The purpose of the article is to determine the complex of symbolic signs of the happiness concept in its structure.